Martians and Venutians in the new world order - Cox, Michael (International affairs (London), 2003)
One of the most significant results of 9/11 has been to provoke the most serious crisis in the transatlantic relationship--the subject of Robert Kagan's influential and provocative treatise. Lauded by some as one of the more important contributions to the study of world politics in recent years and attacked by others as possibly the most misguided analysis of European-American relations ever, Kagan sets forth in stark, realist terms why the rift is serious, long-term and unlikely to be overcome by neat diplomatic footwork. However, as this commentary seeks to show, if Kagan is right there is little chance of constructing anything like a 'new world order'. Moreover, if the clash continues, far from enhancing American power in the world, it is more likely to weaken it. [PUBLICATION ABSTRACT]